The Effects of KEPROGAN® as Feed Additive on Serum Biochemicals and Immune Status of the Chicken - Kadhim, Kadhim Saleh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The purpose of this study was to explore the effect that supplementing broiler chickens with KEPROGAN®® had on their physiological condition as well as their immunological response. The broiler chickens (Ross) were one-day-old when they were randomly divided into two food treatments, each of which contained one hundred chicks. Chickens in group 1 were given a food that contained 0.5% KEPROGAN®®, while chickens in group 2 (the control group) were given a diet that did not contain any supplements. The current study indicated that the supplement KEPROGAN®® provided to broilers resulted in a substantial (P ≤ 0.05) different changes in serum concentration of biochemicals at the end of the study i.e on day 35 with Alkaline Phosphatase (ALP), aspartate aminotransferase (AST), Alanine Transaminase (ALT), Total protein (T.P), Cholesterol, Triglyceride, very low-density lipoprotein (VLDL), Bilirubin, albumin, and globulin), as compared to the control. In contrast to the group that served as the control, an increased in Immunoglobulin IgG titer against ND and IBD virus that was statistically significant (P ≤ 0.05).